Policies and Practices for Hiring Effective Teachers| A Qualitative Study of Louisiana Public Schools - Kling, Gary Andrew, Jr. (University of Louisiana at Lafayette, 2015)
The purpose of this research was to explore individual district hiring policies within Louisiana. The primary question guiding this research was: Is there a particular process currently used by districts in the state of Louisiana that leads to hiring a greater number of effective teachers? Qualitative methodological procedures used in this research explored current policies throughout Louisiana in relation to teacher hiring. Using a case study, data was collected in two phases: (1) an extensive review of the policies in 17 districts; and (2) interviews of five district personnel. The document review uncovered 7 themes and 25 codes essential in the process of hiring teachers. Those themes were: (1) documentation; (2) positions; (3) contracts and compensation; (4) qualifications and duties; (5) recruitment; (6) employment; and (7) assignment. Interviews were used to determine how individual districts were implementing state and federal policy. Finally, three major findings were discovered as a result of the research: (1) Louisiana suffers from pockets of insufficient teacher supply; (2) technology, including social media, can serve as a valuable tool in recruiting and hiring of effective teachers; and (3) no major distinction in hiring practices across districts. An implication for educational leaders include reviewing current policy to eliminate barriers which may prevent the use of technology as a recruiting tool for K-12 educators.